Ants : bio-indicators and metaphors - Said, Aripin; Zamzuri, Azmir (Universiti Putra Malaysia Press, 2013)
Ant is ant insect which has a role in the life of a traditional Malay society. This insect serves as a guidance to determine the seasons and gives the overall picture of the behavioural patterns of the members of its community.When ants of various type and colours move in large numbers, somotimes in the form of a long line, usually they are heading towards higher grounds. Sometimes they climb trees such as the kapok (Ceiba pentandra (L.) Gaertn.) tree and others. When this happens, it indicates that flood will take place.